Management of security activities at innovative-active enterprises - Kopytko, Marta; Fleychuk, Mariya; Veresklia, Mariana; Petryshyn, Nataliia; Kalynovskyy, Andriy (Business: Theory and Practice, 2021)
The article identifies the fundamental problems of innovation as a factor in strengthening the economic security of an enterprise in the context of globalization and integration of the world’s economic space. The factors that have a direct impact on innovation activity both in the country and in the world have been investigated. Clustering of individual countries was carried out and Ukraine’s place among them was determined according to the Global Innovation Index. Using the software packages MS Excel and CurveExpert 5.0, a study of the index of innovative efficiency in Ukraine was carried out; dynamics of financing innovative activities in Ukraine, as well as the impact of the level of capital investment on the volume of financing innovative activities. It is proposed to assess the level of economic security of an enterprise based on indicators of its innovative development. The features of interpreting the concept of “innovative activity of enterprises” have been investigated. The sequence and interconnection of such categories as innovative potential, innovative activity, and innovative activity are analyzed. The structure of the process of innovation activity has been investigated. The rhombus of innovative activity is analyzed, which is formed from the following elements: receptivity to new things – provision of resources – communication and organization of the innovation process – a measure of competence. In the study of the specifics of the management of innovative-active enterprises, the analysis of the features and comparison of the differences between innovation activity and other types of economic activity was carried out. The structure of the process of managing innovatively active enterprises has been developed, taking into account aspects of the safety of activities. The prospect of further research identified a thorough analysis of the features of the management process of innovatively active enterprises, considering the impact of global risks and threats. The principal purpose of the article is to study the essence and main characteristics of innovatively active enterprises in the study’s context of the security aspect.